Conflict Management Strategies in Global Firms - Godiwalla, Yezdi H. (Journal of Management Policy and Practice, 2019)
Conflict management in global firms is more complex and challenging than what it is in domestic firms. The paper focuses upon effective conflict management strategies that first achieve a cessation of hostilities; it then promotes ideas for cooperative behavior. The preferred style of the conflict resolver depends upon the national and organizational cultures, leader (or conflict resolver) and his/her personality (Mo, Booth and Wang, 2012; Oetzel and Wetz, 2012).